2014
DOI: 10.3390/mi5041310
|View full text |Cite
|
Sign up to set email alerts
|

SU-8 Electrothermal Actuators: Optimization of Fabrication and Excitation for Long-Term Use

Abstract: Abstract:In this paper we examine the suitability of SU-8 2000 as a construction material for electrothermal actuators and the actuator stability for long-term operation. The fabrication of SU-8 was optimized for mechanical and thermal stability. Samples with different softbake duration, exposure dose and postbake temperature were evaluated using Fourier-Transform IR-spectroscopy and dynamic-mechanical analysis. The exposure dose and postbake temperature proved to have a strong influence on the cross-linking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Conversely, SEW introduces the ability to modulate viscosity through the degree of crosslinking within the SU-8 solutions. Both SEW and MEW could benefit from further analysis, such as Fourier Transform Infrared Spectroscopy to quantify crosslinking bonds [ 42 , 43 ] and rheological measurements to determine solution viscosity, be it in solution or to further characterize the printable window for thermoset SU-8. Although working with a solution introduces complexities related to charge interactions within the electrowriting setup and the behavior of different chemical species under printing conditions, the potential for achieving diverse construct properties through SEW presents a compelling tradeoff, especially in the case for processability and access to thermoset polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, SEW introduces the ability to modulate viscosity through the degree of crosslinking within the SU-8 solutions. Both SEW and MEW could benefit from further analysis, such as Fourier Transform Infrared Spectroscopy to quantify crosslinking bonds [ 42 , 43 ] and rheological measurements to determine solution viscosity, be it in solution or to further characterize the printable window for thermoset SU-8. Although working with a solution introduces complexities related to charge interactions within the electrowriting setup and the behavior of different chemical species under printing conditions, the potential for achieving diverse construct properties through SEW presents a compelling tradeoff, especially in the case for processability and access to thermoset polymers.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the weight loss of SU-8 could occur above about 277 °C [37], while the simulation result indicated that the temperature near the edges of the membrane could reach 240 °C (see figure 3). Given that the temperature of the onset of weight loss and glass transition of SU-8 depends on its deposition condition [25,28], it was possible that such weight loss or degradation occurred during the measurements, and this may result in a change in the appearance after the measurements. Although the degradation of SU-8 was observed near the edges of the membrane, such degradation can be avoided by improving the design of the device as discussed in the next section.…”
Section: Operation Under a Constant Voltagementioning
confidence: 99%
“…This is approximately 10 times thicker than the typical thickness of the membrane layer. Additionally, SU-8 displays good mechanical stability and was used as a structural material for microfluidic channels [26,27] and actuators [28]. With respect to the thermal properties, SU-8 exhibits a smaller thermal conductivity by approximately an order of magnitude when compared with silicon dioxide (SiO 2 ), which is typically used for the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we chose to work with SU-8, a very popular epoxybased, negative tone resist that can be patterned using photolithography and electron-beam lithography (EBL), 33 which exhibits long-term stability. 34 SU-8 films can be spun at thicknesses ranging from a few tens of nanometers to several hundred micrometers and can produce high aspect ratio features. Additionally, SU-8 has a relatively high average refractive index n p ' 1.58, with a negligible absorption coefficient in the whole visible range.…”
mentioning
confidence: 99%